TECHNICAL AND SCALE EFFICIENCY OF SYARIAH BANKING IN INDONESIA: DATA ENVELOPMENT ANALYSIS APPROACH - Endri Endri; Henny Ritha; Puji Hadiyati (Universitas Hayam Wuruk Perbanas, 2010)
So far, efficiency tends to be a very important issue for discussion. Therefore, such a topic needs attention. This is crucial when it is related syariah banking industry development. In that case, the best performance of shraiah banking can be reached sot hat it has high competitive power in national banking industry. Besides that, it is also expected to be able for expanding the market share. Using the non-parametric method of Data Envelopment Analysis (DEA), this study investigates the recent efficiency of the Islamic Banking operations in Indonesia over the period 2005 to 2007. The attributions of technical efficiency (utilization of capacity) and scale efficiency (optimality of scale achieved) are identified. The principal findings for the period under study indicate that technical and scale efficiency scores are improving but not optimal 100% during research period. The findings provide useful guidelines for policy implications and may also assist banks concerned with their strategic planning with regard to the future of Islamic banking